A genetic variant in microRNA‐122 regulatory region confers risk for chronic hepatitis B virus infection and hepatocellular carcinoma in Han Chinese. Issue 10 (3rd July 2014) - Liu, Yao; Xie, Kaipeng; Wen, Juan; Deng, Min; Li, Jianming; Hu, Zhibin
<x xml:space="preserve">Abstract</x> miR‐122 plays a vital role in the development of chronic hepatitis B virus (HBV) infection and hepatocellular carcinoma (HCC). Based on data from the Encyclopedia of DNA Elements (ENCODE), two single nucleotide polymorphisms (SNPs), rs4309483 and rs4503880, were identified in the upstream regulatory region of miR‐122. A case–control study consisting of 1, 300 HBV‐positive HCC cases, 1, 344 HBV carriers, and 1, 344 persons who cleared HBV naturally was carried out to test the association between the two SNPs and the risk for chronic HBV infection and HCC. The CA/AA genotypes of rs4309483 were associated with significantly increased risk for HCC [adjusted odds ratio (OR) = 1.21, 95% confidence intervals (CIs) = 1.02–1.43, P = 0.025] compared with HBV carriers, but decreased risk for chronic HBV infection (adjusted OR = 0.82, 95% CIs = 0.70–0.97, P = 0.017) compared with persons who cleared HBV naturally. The genotype‐expression correlation between rs4309483 and the expression of primary or mature miR‐122 expression was investigated in 29 pairs of HBV positive HCC and noncancerous liver tissues. In noncancerous liver tissues, subjects carrying the CA genotype exhibited significantly lower expression level of pri‐miR‐122 than those carrying the CC genotype. In addition, positive or inverse correlation between the expression levels of pri‐miR‐122 and mature miR‐122 were observed in HCC tissues or noncancerous tissues, respectively. These findings indicate that the C to A base change of rs4309483 may alter the expression of miR‐122, thus providing protective effect from chronic HBV infection but an increased risk for HCC in HBV carriers. J. Med. Virol. 86: 1669–1674, 2014. © 2014 Wiley Periodicals, Inc.